Successful implementation of an Enhanced Recovery After Surgery program shortens length of stay and improves postoperative pain, and bowel and bladder function after colorectal surgery. Issue 1 (December 2015) - Sarin, Ankit; Litonius, Erik; Naidu, Ramana; Yost, C.; Varma, Madhulika; Chen, Lee-lynn
Abstract Background Despite international data indicating that Enhanced Recovery After Surgery (ERAS) programs, which combine evidence-based perioperative strategies, expedite recovery after surgery, few centers have successfully adopted this approach within the U.S. We describe the implementation and efficacy of an ERAS program for colorectal abdominal surgery in a tertiary teaching center in the U.S. Methods We used a multi-modal and continuously evolving approach to implement an ERAS program among all patients undergoing colorectal abdominal surgery at a single hospital at the University of California, San Francisco. 279 patients who participated in the Enhanced Recovery after Surgery program were compared to 245 previous patients who underwent surgery prior to implementation of the program. Primary end points were length of stay and readmission rates. Secondary end points included postoperative pain scores, opioid consumption, postoperative nausea and vomiting, length of urinary catheterization, and time to first solid meal. Results ERAS decreased both median total hospital length of stay (6.4 to 4.4 days) and post-procedure length of stay (6.0 to 4.1 days). 30-day all-cause readmission rates decreased from 21 to 9.4 %. Pain scores improved on postoperative day 0 (3.2 to 2.1) and day 1 (3.2 to 2.6) despite decreased opioid. Median time to first solid meal decreased from 4.7 to 2.7 days and duration of urinary catheterization decreased from 74 to 46 h. Similar improvements were observed in all other secondary end points. Conclusions These results confirm that a multidisciplinary, iterative, team-based approach is associated with a reduction in hospital stay and an acceleration in recovery without increasing readmission rates.